Yahoo Web Search

  1. Ad
    related to LHS
  1. Sort by

  1. ... to "solve" the equation, instead of "proving" it. LHS = (csc A + cot A) (1 − cos A) − (sec A + tan A...

    5 Answers · Science & Mathematics · 08/01/2018

  2. secx = 1/cosx, so considering the LHS we have: cosx - (1/cosx) => (cos²x - 1)/cosx Now, sin²x...

    4 Answers · Science & Mathematics · 04/01/2018

  3. L.H.S. = (√(4 - √7)) = (√7 - 1)/√2 R.H.S. = (√(8 + 3√7) - 2√2)) = (√7 - 1)/√2 Hence LHS = RHS

    7 Answers · Science & Mathematics · 03/01/2018

  4. LHS = sin²x + (a+b)sinxcosx + abcos²x = ½{ (1+ab) + (a+b...2x) = √{(a+b)²+(ab−1)²}sin(2x+α) where tanα = (ab−1)/(a+b) ∴ LHS ≤ = ½{ (1+ab) + √{(a+b)²+(ab−1)²} } since sin≤1...

    1 Answers · Science & Mathematics · 30/12/2017

  5. LHS = { a(1−b²)(1−c²) + b(1−a²)(1−c²) + c(1...3w Numerator = wv−(uv−3w)+u = (w−u)(v−1)+4w = 4w since w=u ∴ LHS = 4abc/{(1−a²)(1−b²)(1−c²)}

    1 Answers · Science & Mathematics · 27/12/2017

  6. ...pi/6)-/+(pi/3) => k={[(-1)^k]-/+2} /6 The result is impossible for the LHS is an integer while the RHS is a fraction=> no integral k...

    2 Answers · Science & Mathematics · 26/12/2017

  7. ... easy by Jensen using the convex function 1/√x (x>0) LHS is homogeneous so you can assume that a+b+c=1 and then apply Jensen with...

    2 Answers · Science & Mathematics · 19/12/2017

  8. LHS = cos(A+B) cos( A-B) =(cosAcosB - sinAsinB...

    3 Answers · Science & Mathematics · 08/12/2017

  9. LHS = 1 - [ (sin²x tanx ) / (tanx + 1) ] - [ cos²x / (tanx + 1) ] = [( tanx...

    2 Answers · Science & Mathematics · 08/12/2017

  10. LHS= cos(x-pi/2)/sin(x-pi/2)= [cos(x)*0+sin(x)*1]/ [sin(x)*0-cos(x)*1]= sin(x)/[-cos(x)]= -tan(x)= RHS.

    4 Answers · Science & Mathematics · 12/01/2018

  1. Ads
    related to LHS
  1. Try asking your question on Yahoo Answers